Environment-Friendly Cotton Production through Implementing Integrated Pest Management Approach (The Pakistan Development Review, 2007)
Tremendous increases in pesticide use in cotton growing areas have severely affected the health of peoples and degraded environment [Poswal and Williamson (1998); Ahmad and Poswal (2000); Orphal 2001 and Khan (2000)]. Farmer Field School (FFS) based IPM implemented in the world to reduce dependence on pesticides and promote environmentally safe plant protection practices. An FFS-led Integrated Pest Management (IMP) model implemented in Pakistan during 1996—popularly known as “Vehari Model”, clearly demonstrated that IPM could be implemented on a large scale at the farm level. UNDP-FAO Policy Reform Project provided required policy level support to scale up the Farmer-led IPM in the country. Implementation of pesticide policy project in Pakistan highlighted that pesticide consumption increased from 665 metric tons in 1980 to 78,132 metric tons in 2003-4. The role of private sector in promoting the production and use of pesticides was found tremendously high. The private sector also took full advantage of government’s pesticide import liberalisation policies. One of the key components of dramatic increase in pesticide use in Pakistan is related to very soft import and registration at that time, which allowed the generic compounds registered elsewhere, to be imported without fieldtesting.